Factors Associated With Underprivileged E-Learning, Session Jam Phobia, and the Subsequent Mental Distress Among Students Following the Extended University Closure in Bangladesh - Hossain, Md. Jamal; Ahmmed, Foyez; Sarker, Md. Moklesur Rahman; Sarwar, Sneha; Bari, Md. Sazzadul; Khan, Md. Robin; Shahriar, Saimon; Rafi, Md. Oliullah; Emran, Talha Bin; Mitra, Saikat; Islam, Md. Rabiul; Mohamed, Isa Naina (Frontiers in Public Health, 2022)
Severe session jam phobia (SJP), the extent of underprivileged online education, and subsequent mental health disorders among students have emerged as distinguished global problems due to the overwhelming effects of coronavirus disease 2019 (COVID-19). The purpose of this research was to evaluate the impact of extended COVID-19 lockdown and its mediating factors on current e-Learning activities, the prevalence of severe SJP and psychological distress among university students in Bangladesh. A web-based cross-sectional study was conducted to assemble responses through Google Form by applying a simple snowball sampling technique among university students aged 18 years or above in Bangladesh. All ethical considerations were maintained, and univariate, bivariate, and multivariate analyses were employed to analyze the acquired data set. Among the total analyzed data (n = 1,122), the male and female ratio was almost 1:1, and a remarkable segment (63.7%) was aged between 21–24 years. Alarmingly, around 50–60% of the students were suffering from severe SJP, prevailing underprivileged education in the e-Learning platform, and severe mental distress. Logistic regression analyses demonstrated that the students from public universities, lower- and mid-income families, lower-aged, and junior years education groups were significantly (p < 0.05) more underprivileged than their counter groups. Besides, the monthly family income and university type significantly influenced the extent of severe SJP. Finally, the students who were female, rustic, come from low-income families (below 25,000 BDT), who had academic uncertainty, job insecurity, online exam phobia, and dissatisfaction with e-Learning education, were significantly suffering from moderate to severe mental distress. The current evidence demonstrates that a substantial number of Bangladeshi university students are struggling with extreme session jam phobia, underprivileged e-Learning education, and subsequent psychological distress, which need to be immediately addressed through concerted efforts by the government, parents, and university authorities.